Revitalizing the Role and Function of the Mosque as a Center for Da'wah Activities and Community Development - Usman, Iskandar (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2020)
Prophet Muhammad SAW was the first to build a mosque and he has given a very strategic role to the mosque and functioned optimally as a center for da'wah and fostering activities of the people. The Prophet Muhammad SAW was the bearer of the Divine message which was the most successful in conveying Islamic teachings and the most successful in fostering the Ummah. In less than 23 years, Rasulullah SAW succeeded in conveying the teachings of Islam perfectly and gained a very large number of followers and at the same time managed to foster the ummah into a civil society with high civilization and noble character. From one of the first mosques built by Rasulullah SAW in Quba, there are now millions of mosques throughout the world. But the role and function of mosques, in general, have experienced a lot of degradation, less functioning as a center of worship and Islamic culture, as practiced by Rasulullah SAW, more mosques only function as places of worship, instead, there are mosques which are only used as places for Friday prayers, whereas prayer the other five times are not held in the mosque in the congregation, because Muslims are not disciplined in keeping their prayers in congregation. This article would like to convey some thoughts, ideas, and ideas for the revitalization of the mosque as a center for preaching and fostering activities of the people.